2018
DOI: 10.3389/fnana.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Structural Connectivity of the Anterior Cingulate Cortex, Claustrum, and the Anterior Insula of the Mouse

Abstract: The claustrum is a narrow subcortical brain structure that resides between the striatum and insular cortex. The function of the claustrum is not fully described, and while our previous work supports a role for the claustrum in top-down cognitive control of action, other evidence suggests the claustrum may be involved in detecting salient changes in the external environment. The anterior cingulate cortex (ACC) and the anterior insular (aINS) are the two major participants in the salience network of human brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 48 publications
6
36
0
Order By: Relevance
“…Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons. Strong connectivity between the cingulate cortex and the claustrum–endopiriform complex was reported previously (Behan & Haberly, ; Condé et al, ; Qadir et al, ; Smith et al, ; Wang et al, ; Watson et al, ; White et al, ; Zingg et al, ), confirming our observations that these GFP pos neurons are located within the endopiriform nucleus. The endopiriform nucleus is strongly connected to the amygdaloid complex, therefore retrograde labeling of amygdalar projection neurons could further corroborate our finding that GFP pos neurons are located within the endopiriform nucleus (Majak et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons. Strong connectivity between the cingulate cortex and the claustrum–endopiriform complex was reported previously (Behan & Haberly, ; Condé et al, ; Qadir et al, ; Smith et al, ; Wang et al, ; Watson et al, ; White et al, ; Zingg et al, ), confirming our observations that these GFP pos neurons are located within the endopiriform nucleus. The endopiriform nucleus is strongly connected to the amygdaloid complex, therefore retrograde labeling of amygdalar projection neurons could further corroborate our finding that GFP pos neurons are located within the endopiriform nucleus (Majak et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous reports on PV expression in the nucleus endopiriformis (Real, Dávila, & Guirado, 2003;Wang et al, 2017), we only found scarce immunoreactivity to PV in the region with the highest density of GFP pos neurons (Figure 1b). Furthermore, previous studies reported on a strong connectivity between the claustrumendopiriform complex and the anterior cingulate and infralimbic cortex (Behan & Haberly, 1999;Condé, Maire-Lepoivre, Audinat, & Crépel, 1995;Qadir et al, 2018;Smith et al, 2018;Wang et al, 2017;White et al, 2017;Zingg, Dong, Tao, & Zhang, 2018). Therefore, we injected a DiI crystal into the anterior cingulate cortex and determined the presence of DiI-positive fibers in the area with the highest density of GFP pos neurons (Supporting Information Figure S2).…”
Section: Gfp Pos Cells Are Located In the Endopiriform Nucleusmentioning
confidence: 99%
“…In rats, there does not appear to be anatomical connectivity between the CPu and claustrum (Smith and Alloway, 2010), suggesting that CPu and claustrum should have low RSFC. Some connectivity between Ins and claustrum may exist in in rats (Lipowska et al, 2000; Qadir et al, 2018), which may suggest that some Ins-claustrum FC could have been suppressed with SRCC. Limited RSFC between the claustrum and endopiriform nucleus is also expected given that the endopiriform nucleus and claustrum have distinct anatomical connectivity patterns in mice (Watson et al, 2017; Qadir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Each ROI (eight total: bilateral claustrum, Ins, CPu and Endo) was hand drawn on the previously described template brain resliced to 0.3 mm isotropic voxels (Figure 1A). We identified the claustrum based on known anatomical boundaries of the claustrum and used a parvalbumin staining from a separate dataset as a molecular marker for the claustrum (Qadir et al, 2018). The volume of each (i.e., left and right) claustrum was 2.86 mm 3 , or about 18 native resolution voxels.…”
Section: Methodsmentioning
confidence: 99%
“…A role in attention is implicated by the participation of CLA in resilience to distraction during a behavioral task (Atlan et al, ). Recent work supports a role for CLA in stimulus salience via reciprocal connections with anterior cingulate cortex (Qadir et al, ; White et al, ). All of these theories derive from the assumption that there is a single discoverable function of the CLA that will be the same across species.…”
Section: Discussionmentioning
confidence: 84%